Analysis of Determinants of Competitiveness of Small Industries Using Fuzzy AHP Approach (Case Study At Mandiri Mitra Sejati Balikpapan) - Tunggul Parasian Lumbantobing; Arini Anestesia Purba; Alvin Muhammad ‘Ainul Yaqin (G-Tech: Jurnal Teknologi Terapan, 2025)
UMKM Mandiri Mitra Sejati Balikpapan is a local business engaged in non-metallic mining in the form of handmade brick crafts. This SME faces challenges such as the use of traditional technology, low human resource competence, waste management, and suboptimal production efficiency. This study aims to identify and analyze priority factors, as well as formulate strategies to enhance competitiveness using the Fuzzy Analytical Hierarchy Process (Fuzzy AHP) approach. Research data was obtained through interviews and the distribution of questionnaires to six respondents, including 1 owner and 5 workers, analyzed into three different weighting scenarios: 60:40, 75:25, and 50:50. The results of this study indicate that the Quality Criteria (K4) is the most dominant factor in determining competitiveness with a weight of approximately 0.4043-0.4107, followed by the Human Resources Criteria (K3) with a weight of approximately 0.3135-0.3328. The most significant sub-criteria are in the quality aspect of the production process. The sensitivity analysis results reinforce Criteria K4 and K3 as the main factors. The recommended strategy is to improve production quality through employee training programs and operational technology modernization. The results of this study are expected to serve as a basis for strategic decision-making by similar SMEs to enhance their competitiveness.